Writing the South through the self : explorations in southern autobiography - Inscoe, John C., 1951- (University of Georgia Press, 2011)
Drawing on two decades of teaching a college-level course on southern history as viewed through autobiography and memoir, John C. Inscoe has crafted a series of essays exploring the southern experience as reflected in the life stories of those who lived it. Constantly attuned to the pedagogical value of these narratives, Inscoe argues that they offer exceptional means of teaching young people because the authors focus so fully on their confrontations--as children, adolescents, and young adults--with aspects of southern life that they found to be troublesome, perplexing, or challenging. Maya Angelou, Rick Bragg, Jimmy Carter, Bessie and Sadie Delany, Willie Morris, Pauli Murray, Lillian Smith, and Thomas Wolfe are among the more prominent of the many writers, both famous and obscure, upon whom Inscoe draws to construct a composite portrait of the South at its most complex and diverse. The power of place; struggles with racial, ethnic, and class identities; the strength and strains of family; educational opportunities both embraced and thwarted--all are themes that infuse the works in this most intimate and humanistic of historical genres. --From the back of book.